Essays in domestic and international finance. - Federal Reserve Bank of New York. ([New York, 1969)
This booklets reveals some of the current happening in federal reserve bank of New York in 1969. The paper further examined the domestic and international financial system in relation to the policy of the bank.
Bibliographical footnotes.
asm; 05/03/19
Loans
Keywords: Finance; International finance